2010
DOI: 10.1177/152692481002000412
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Organ Donation and Donor Behavior: A Review of the International Literature

Abstract: The review revealed the complexity of individuals' attitudes toward donation and the need for more sophisticated future studies of the interactions between the broader factors influencing donation (such as social norms and existing legislation in each country) and individual factors, such as attitudes and beliefs. (Progress in Transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 40 publications
4
69
1
6
Order By: Relevance
“…It would therefore appear that educational interventions associated with prior preparation could increase the rate of consent to organ donation. While public campaigns may be helpful in promoting organ donation generally, community educational intervention may be more productive in challenging cultural attitudes and beliefs (Wakefield, Watts, Homewood, Meiser, & Siminoff, 2010), for example, reported misconceptions about religious perspectives and donor age. Raising public knowledge and awareness is essential to the provision of informed choice for family members, in overcoming their fears and concerns, and in reducing elements of surprise when approached about organ donation.…”
Section: Discussionmentioning
confidence: 97%
“…It would therefore appear that educational interventions associated with prior preparation could increase the rate of consent to organ donation. While public campaigns may be helpful in promoting organ donation generally, community educational intervention may be more productive in challenging cultural attitudes and beliefs (Wakefield, Watts, Homewood, Meiser, & Siminoff, 2010), for example, reported misconceptions about religious perspectives and donor age. Raising public knowledge and awareness is essential to the provision of informed choice for family members, in overcoming their fears and concerns, and in reducing elements of surprise when approached about organ donation.…”
Section: Discussionmentioning
confidence: 97%
“…3 In this sense, a favorable attitude toward organ donation has been found in more than 75% of respondents and it is similar to that described in some population groups that are not related to donation and transplantation. [11][12][13][14] These data are not universal and cannot be generalized in all areas, and important variations exist from one country to the next. Of particular note is that in Spain, one of the countries included in the study and which has one of the highest deceased donation rates in the world, the attitudes of health care workers are among least favorable.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are generally consistent with previous studies on willingness to donate. 9,11,12,17 More importantly, we found that there is a more than two-fold variation across DMVs in rates of organ donor designation. Use of SDDRs that adjust for characteristics of DMV patrons greatly reduced this variation and may more accurately describe the performance of DMVs in promoting organ donation.…”
Section: Discussionmentioning
confidence: 66%